Optimization of The Proportion of Salted Egg in the Crackers Making Process in terms of Crispness, Nutritional Value, and Hedonic - Bintoro, Valentinus Priyo; Pramesti, Gabriela Wina Ayu; Susanti, Siti; Rohmat, Yusup Nur Nur; Sarjana, Teysar Adi (Lembaga Penelitian dan Pengabdian Masyarakat, Institut Teknologi Sumatera, 2023)
Crackers are one of the foods that are in demand by all circles of society. Salted egg crackers are an innovative product of egg crackers made from duck eggs. Salted egg crackers are made from duck eggs that are processed into salted eggs then mixed with tapioca starch and added with other spices to improve the flavor and nutritional content. This study aims to determine the effect of different proportions of salted eggs on the nutritional content, physical quality, and consumer liking of salted egg crackers. There are 5 treatments of different proportions of eggs, namely 0 g (To ), 62.5 g (T1), 125 g (T2), 187.5 g (T3), and 250 g (T4). The research method consists of experimental design, research procedures, parameter analysis and data analysis. The results of the analysis showed that the difference in the proportion of salted egg addition to salted egg crackers affects the levels of protein, ash, fat, and calories. The higher proportion of salted egg will make protein and ash levels increase, while fat and calorie levels decrease. Physical and hedonic analysis showed that the highest crispness and most preferred by panellists overall was found in the proportion of salted egg 125 g (T2). In conclusion, optimising the proportion of salted egg at 48% or 125 g of 387 g total dough produces good quality and crispy crackers.